THE IMPACT OF EMOTIONAL DISCLOSURE TRAINING ON EMOTIONAL EXPRESSION OF UNIVERSITY STUDENTS - Yücel ÖKSÜZ (Fırat University, 2019)
This study aims to discover the impact of training program about the emotional disclosure, developed by the researcher on the undergradutes’ emotional disclosure. The research was designed in post test and pre-test experimental study with control group. 48 undergradute students, 24 of them experimental gruop and control group, participated the study. The data was obtained through “the Emotional Expression Scale” developed by King & Emmons and adapted by Kuzucu (2006). The Scale consists of three subdimensions. Its Cornbach Alpha Coefficient is .85. The data was analyzed through the independent t-test. The finding indicated that the experimental group scored higher than the control group in the post-test. This finding also proved that the training program about the emotional disclosure can be considered as effective on the undgraduates’ emotional disclosure and expression. Results from the study was discussed in the light of literature and several suggestions were made.